Activation of SIRT1 Attenuates Klotho Deficiency–Induced Arterial Stiffness and Hypertension by Enhancing AMP-Activated Protein Kinase Activity. Issue 5 (November 2016) - Gao, Diansa; Zuo, Zhong; Tian, Jing; Ali, Quaisar; Lin, Yi; Lei, Han; Sun, Zhongjie
Abstract : Arterial stiffness is an independent risk factor for stroke and myocardial infarction. This study was designed to investigate the role of SIRT1, an important deacetylase, and its relationship with Klotho, a kidney-derived aging-suppressor protein, in the pathogenesis of arterial stiffness and hypertension. We found that the serum level of Klotho was decreased by ≈45% in patients with arterial stiffness and hypertension. Interestingly, Klotho haplodeficiency caused arterial stiffening and hypertension, as evidenced by significant increases in pulse wave velocity and blood pressure in Klotho-haplodeficient ( KL +/– ) mice. Notably, the expression and activity of SIRT1 were decreased significantly in aortic endothelial and smooth muscle cells in KL +/– mice, suggesting that Klotho deficiency downregulates SIRT1. Treatment with SRT1720 (15 mg/kg/d, IP), a specific SIRT1 activator, abolished Klotho deficiency–induced arterial stiffness and hypertension in KL +/– mice. Klotho deficiency was associated with significant decreases in activities of AMP-activated protein kinase α (AMPKα) and endothelial NO synthase (eNOS) in aortas, which were abolished by SRT1720. Furthermore, Klotho deficiency upregulated NADPH oxidase activity and superoxide production, increased collagen expression, and enhanced elastin fragmentation in the media of aortas. These Klotho deficiency–associated changes were blocked by SRT1720. In conclusion, this study provides the first evidence that Klotho deficiency downregulates SIRT1 activity in arterial endothelial and smooth muscle cells. Pharmacological activation of SIRT1 may be an effective therapeutic strategy for arterial stiffness and hypertension. Abstract : Supplemental Digital Content is available in the text.